The Impact of CD4 Count Level on Patterns of Respiratory Tract Infections of HIV-Infected Patients: A Study in Western India - Shah, Rajeev Ramanlal (Medical Science: Trends and Innovations Vol. 7, 2025)
Background: The World Health Organisation has estimated that 25 million people have died of HIV/AIDS, including 2 million people who died in 2007. A significant proportion of these deaths were due to opportunistic pneumonias. The majority of new HIV infections are in adults aged 20 to 39 years old. Individuals with HIV infection are at increased risk for tuberculosis (TB) and other respiratory tract infections (RTIs). The altered CD4 T-cell homeostasis induced by HIV infection may play a key role in the development of respiratory tract infections in HIV-infected patients. Aim: The aim of the study is to find out of mean CD4 count of HIV patients at which they were at higher risk of developing various RTIs and accordingly when HAART is to be started in this part of the world. Materials and Methods: The present prospective study was conducted between 9th August 2009 to 23rd January 2012. All the 961 HIV-infected patients and 300 HIV seronegative patients’ three early morning sputum were screened for routine bacterial and fungal pathogens and even examined for AFB and few of the samples were even cultured on LJ medium. All sputum samples’ smears were also examined for Poly Morpho Nuclear Leucocytes (PMNLs) in Gram staining. Results: Out of all these 961 HIV patients, those with probable viral respiratory tract infections (RTIs) (349 patients) had a mean CD4 count of 474.62 ± 114.89, followed by mixed polymicrobial RTI (80 patients) with mean CD4 about 392.26 + 87.14. For the patients with pure fungal etiology (66), the mean CD4 count was found to be 377.29 + 268.29 followed by 466 patients with pure monomicrobial bacterial RTI the mean CD4 count was about 223.07 + 83.21. Conclusion: A very vague co-relationship between the pattern of RTIs and CD4 counts has been attempted. Only Fungal and Bacterial RTIs were seen first to establish in even HIV-infected patients at very high mean CD4 counts of about 377 + 268.29 and 223.07 + 83.21 respectively, but in both very high prevalence rates were observed when compared with HIV non-infected patients with probability values of <0.05 and <0.001 respectively. The probable viral etiology of RTI was significantly high in HIV-non infected subjects when compared to HIV-infected RTI patients with a probability value of P < 0.001.